PREDISPOSITION IN THE ACQUISITION OF THE ENGLISH LANGUAGE IN CHILDREN WITH AUTISM SPECTRUM DISORDER COMPARED TO MOTOR PERFORMANCE: CROSS-SECTIONAL STUDY. (CIPEEX, 2022)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder where there is a disruption in the fundamental processes of socialization, communication, and learning. A percentage of autistic individuals do not develop speech, and when it occurs, it is typically altered; however, there are reports of a predisposition to learning a second language to the detriment of the first. Objective: To evaluate the predisposition for acquiring English as a second language and motor development in Brazilian children with ASD. Materials and method: The cross-sectional study had a convenience sample composed of 16 children diagnosed with ASD, with chronological ages between 6 and 11 years old. After being approved by the Ethics and Research Committee of UniEVANGÉLICA and constituted by screening, the participants took a placement test where their level of confidence and fluency in the English language was assessed. For the motor assessment, the Revised Psychoeducational Profile (PEP-R) (Schopler, Reichler, Bashford, Lansing & Marcus, 1990) was applied, aiming to evaluate the developmental age in seven areas: imitation, fine motor coordination, gross motor coordination, visuomotor coordination, perception, cognitive performance, and verbal cognition. Results: The results will be statistically analyzed assuming a significance level of p≤0.05, with the aim of promoting communication and cognitive interventions and providing a better quality of life in the language development of the autistic child.
Keywords: Bilingualism; Verbal Fluency; Autism Spectrum Disorders